Hubungan Pola Asuh Orang Tua terhadap Kepatuhan Penerapan Protokol Kesehatan pada Anak Usia Sekolah di Era New Normal - I Putu Permana Adi Wijaya; Ni Luh Kompyang Sulisnadewi; I Ketut Labir (Jurnal Gema Keperawatan, 2022)
Compliance of health protocols implementation on school age children in the new  normal era influenced by many factors, one of which is parents parenting. The purpose of this study was to determine the relation between parents parenting with compliance of health protocols implementation on school age children in the new normal era. The research was conducted at SD No. 4 Mengwi in 2021. The research design used correlational analytic with cross-sectional design. The sample in this study amounted to 97 people using simple random sampling technique. Parenting patterns were measured using a parenting style questionnaire, compliance of health protocols implementation was measured using a health protocols questionnaire. The results showed that 50.5% were male, 36.1% were 11 years old. 92.8% of the parenting characteristic was point to democratic parenting. The category compliance of health protocols implementation, obedient was 3.1% in authoritarian parenting, obedient was 92.8% in democratic parenting, and unobedient was 4.1% in permissive parenting. Chi square test results obtained values of r +0.765 and sig. = 0.000 (α=0.050). The conclusions that there are strong, positive, and significant relation between parents parenting with compliance of health protocols implementation.